2017
DOI: 10.1002/cyto.a.23170
|View full text |Cite
|
Sign up to set email alerts
|

Development of a bead‐based multiplexed assay for simultaneous quantification of five bovine cytokines by flow cytometry

Abstract: Quantifying cytokines is extremely important in studies of host-pathogen interactions. Multiplex assays are commercially available but only for human and mouse cytokines. Here a method for the simultaneous quantification of five important bovine cytokines IFNγ, IL-4, IL-10, IL-12, and TNFα in cell culture supernatants, using flow cytometry was reported. Functional beads from BD Biosciences expressing specific APC intensity were used. Commercially available antibodies against bovine cytokines were covalently co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…S2 ) and performed on the same sample. The reasons for choosing the flow method are as follows: (1) Wider dynamic range ( Rodrigues et al, 2017 ). (2) By using different magnetic beads and decoding methods, bead-based flow cytometry can be easily extended to detect multiple biomarkers simultaneously.…”
Section: Resultsmentioning
confidence: 99%
“…S2 ) and performed on the same sample. The reasons for choosing the flow method are as follows: (1) Wider dynamic range ( Rodrigues et al, 2017 ). (2) By using different magnetic beads and decoding methods, bead-based flow cytometry can be easily extended to detect multiple biomarkers simultaneously.…”
Section: Resultsmentioning
confidence: 99%
“…On the contrary, the meta-analysis of studies using bead-based assays found no difference in IL-4 levels between patients with severe malaria and those with uncomplicated malaria. A study suggested that the two methods were comparable, but a bead-based assay could detect the bovine cytokine IL-4 and other cytokines, such as IFN-γ, IL-10, IL-12, and TNF-α, in a wider dynamic range than ELISA [ 54 ]. Addionally, ELISA is easy to use and robust for measuring single cytokines, but bead-based assays can be multiplex immunoassays to detect several cytokines in a single run [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed a good correlations between standard ELISA and CBA assays on cytokines [19,20]. Multiplex flow cytometry assay can be a useful tool to measure a large number of pro and anti-inflammatory cytokines concentration in LPS-stimulated RAW 267.4 macrophages in a short period of time [21].…”
Section: Multiplex Flow Cytometry Bead Assaymentioning
confidence: 92%